Elucidation of myricetin biosynthesis in Morella rubra of the Myricaceae. (20th September 2021) - Xing, Mengyun; Cao, Yunlin; Ren, Chuanhong; Liu, Yilong; Li, Jiajia; Grierson, Donald; Martin, Cathie; Sun, Chongde; Chen, Kunsong; Xu, Changjie; Li, Xian
SUMMARY: Flavonols are health‐promoting bioactive compounds important for plant defense and human nutrition. Quercetin (Q) and kaempferol (K) biosynthesis have been studied extensively while little is known about myricetin (M) biosynthesis. The roles of flavonol synthases (FLSs) and flavonoid 3′, 5′‐hydroxylase (F3′5′H) in M biosynthesis in Morella rubra, a member of the Myricaceae rich in M‐based flavonols, were investigated. The level of MrFLS transcripts alone did not correlate well with the accumulation of M‐based flavonols. However, combined transcript data for MrFLS1 and MrF3′5′H showed a good correlation with the accumulation of M‐based flavonols in different tissues of M. rubra . Recombinant MrFLS1 and MrFLS2 proteins showed strong activity with dihydroquercetin (DHQ), dihydrokaempferol (DHK), and dihydromyricetin (DHM) as substrates, while recombinant MrF3′5′H protein preferred converting K to M, amongst a range of substrates. Tobacco ( Nicotiana tabacum ) overexpressing 35S::MrFLSs produced elevated levels of K‐based and Q‐based flavonols without affecting M‐based flavonol levels, while tobacco overexpressing 35S::MrF3′5′H accumulated significantly higher levels of M‐based flavonols. We conclude that M accumulation in M. rubra is affected by gene expression and enzyme specificity of FLS and F3′5′H as well as substrate availability. In the metabolic grid of flavonol biosynthesis, the strong activity of MrF3′5′H with K as substrate additionally promotes metabolic flux towards M in M. rubra . Significance Statement: Myricetin is an important flavonol with various human health benefits; however, how plants make myricetin remains unclear. Both MrFLS and MrF3′5′H activity are essential in myricetin biosynthesis, where F3'5'H is postulated to be important for driving metabolic flux towards the trihydroxylated flavonol by hydroxylating kaempferol without the need of a DHM‐specific FLS in Morella rubra .